Technology of cream soups using innovative culinary semi-finished goods - Vasilenko, Victoria; Pushka, Olga; Havrysh, Andrey; Ishchenko, Tatiana; Niemirich, Oleksandra (My University, 2016)
The article presents the urgency of the use of innovative culinary semi-finished products in the technology of mashed soup.
Keywords: технологія; технология; technology; суп-пюре; суп-пюре; soup; кулінарний напівфабрикат; кулинарный полуфабрикат; culinary semi-finished product; кафедра готельно-ресторанної справи